Survival strategy. The Death Brigade by Leon Weliczker - Przymuszała, Beata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article discusses the account by Leon Weliczker (The Death Brigade) who belonged to the Sonderkommando in the Janowska camp. When describing everyday life centring on the removal of corpses, Weliczker also revealed his own methods for survival. Trauma discourse focusses on trauma’s later influence, in the case of the analysed text that applies to an attempt at recording a continuing traumatic state. In applying the psychological context, the author indicates how Weliczker tried to minimise the influence of trauma by utilising various mechanisms for controlling and suppressing emotions.